STIGMA IN DEMENTIA: ITS TIME TO TALK ABOUT IT - Harper, L A (Innov Aging, 2018)
There is considerable evidence that the combined impact of having a dementia and the negative response to diagnosis and symptoms significantly undermines psychosocial well-being and quality of life. There is growing evidence that stigma emphasizes and deepens this distress, yet we still know very little about the stigma experienced by persons with dementia (PwD) and their care partners. In this symposium, participants will learn about the types of stigma and how the experience of stigma interferes with attaining appropriate services, lowers quality of life, is associated with many mental health issues in PwD, and may be affected by novel advances in early diagnosis. In addition, coping styles and years of education may influence the experience of stigma by care partners. Attendees will learn that stigma is pervasive worldwide and may be more severe in some ethnic groups. Through data collected from an ongoing blog, participants will get an opportunity to hear personalized stories from PwD that highlight who they were before the disease and how things have changed. Participants will also understand the considerable variability in the general public’s knowledge of dementia which can contribute to the experience of stigma by PwD and their care partners. Stigma assessment tools and experimental approaches to assess or manage stigma will be reviewed. Interventions will be discussed that may lower the stigma experience including the results from a pilot study that introduces educational curriculum to address dementia-related stigma.